Benthic metabolism and nutrient dynamics of a hyperturbid and hypernutrified estuary - Perez-Rodriguez, Valle; Corzo, Alfonso; Papaspyrou, Sokratis; van Bergeijk, Stefanie Anne; Vilas, Cesar; Cañavate, José Pedro; Garcia-Robledo, Emilio (Frontiers in Marine Science, 2024)
The biogeochemical role of the sediments in the Guadalquivir River estuary, a vital region in the SW Iberian Peninsula, has been considerably neglected. The benthic microalgae (microphytobenthos, MPB) inhabiting the sediment surface could contribute to the autochthonous primary production and influence nutrient recycling in this hyper-turbid and hypernutrified estuary. Sediment-water column fluxes of O2 and dissolved inorganic nitrogen species (DIN=NH4 + +NO3 -+NO2 -) were assessed in laboratory incubations of sediment cores from Bonanza (mouth) and Lebrija (middle) during a oneyear study. Vertical profiles down to 10 cm depth of photosynthetic pigments, organic C, total nitrogen, DIN, Fe 2+ , SO4 2-, and dissolved inorganic carbon (DIC) were also measured. Chlorophyll a in the sediment surface was higher at the estuarine mouth, exhibiting a seasonal pattern at both sites with highest values in winter and lowest in summer. Net community production (NCP) was higher in Bonanza compared to Lebrija and showed positive values most of the year, indicating that MPB contributed to the overall autochthonous primary production of the estuary. Seasonal changes in chlorophyll a and NCP were not parallel, suggesting different ecological controls. The sediment was generally a net sink of NO3 -and NH4 + in both sites, with several fold higher rates for NO3 -uptake. MPB N-demand could account for the entire sediment DIN uptake in Bonanza and 21% in Lebrija. The remaining high NO3 -uptake rates indicate that they sustain elevated sediment denitrification rates. In contrast, rates of anaerobic oxidation of organic matter by Fe-reduction and SO4 2–reduction, estimated from Fe 2+ and SO4 2-vertical concentration profiles, were several orders of magnitude lower than the estimated water column-dependent denitrification rates. Overall, this study shows the importance of MPB in the Guadalquivir Estuary and the potential dominant role of denitrification in the anaerobic mineralization of organic matter.